The Relationship Between Dysbiosis in Geriatrics and the Risk of HMPV: A Literature Review - Adnexa Miftah Firdausy; Adib Danurdipta; Jodii Arlan Kurnia (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study investigates the relationship between dysbiosis in the geriatric population and the increased risk of Human Metapneumovirus (HMPV) infection through a literature review. The aim of the study is to identify the underlying pathophysiological mechanisms by which dysbiosis affects the immune system, particularly via the gut-lung axis, and its implications for HMPV infection risk. A systematic review was conducted on reputable journals published over the last 10 years (2015–2025) by searching PubMed, Scopus, and ScienceDirect using the keywords